Aplicación de los saberes previos para mejorar la comprensión de textos escritos en inglés en estudiantes de segundo grado de secundaria en la Institución Educativa Inicial Primaria Secundaria 60014 Santo Cristo de Bagazan Belén 2023 - Tamani Linares, Ruth Priscilla (2025)
The objective of this research study was to assess the effectiveness of a learner training program based on strategies of self-study to develop understanding written English texts in second-grade secondary school students at 60014 Santo Cristo de Bagazan school, Belén 2023. The study is evaluative type, with research designs of: Field-based, contemporary transactional, univariable, and quasi experimental, with pre-test, post-test, and control group. The study population was made up by 213 students and a non-probabilistic sample 75 divided into two groups: the control group consisting of 37 students, while the experimental group consisted of 38 students. The data gathering tool was a valid and reliable achievement written test. After developing the program, the result show that the experimental group outperformed the control group as their mean score in reading comprehension was higher 16.569 in contrast to the control group, which achieved a average of 9.080 on the 0-20 vigesimal scale. As well as in its dimensions: Gets information (17.103 > 10.806), Infers and Interprets (17.222 > 7.949), Evaluates the form, content and context (15.509 > 7.821). In conclusion, finally, of the Mann Whitney U test demonstrated that the educational program of prior knowledge significantly improves the understanding of written texts, as the p-value was 0.000 < α=0.05 level of significance, accepting the alternative hypothesis.